Good laws, bad outcomes: land rights and inheritance practices for Christian women in Bangladesh. Issue 2 (3rd May 2016) - Das, Joyce
ABSTRACT: This paper explores a critical gender issue: women's land rights in the context of legal pluralism, focusing on the minority Christian community in Bangladesh. While the Christian Personal Law in Bangladesh provides substantial inheritance rights, in practice most women fail to exercise these rights. This paper shows that women's land (dis)inheritance is closely linked with processes of identity creation and protection. Linking theories of legal pluralism with community identity and gender, this paper argues that the patriarchal Bangladeshi Christian community use, alter, or locally create the law to protect their identity as a religious minority community at the expense of women's land rights. On the basis of my ethnographic research carried out in Bangladesh, I also examine the consequences of gender inequality in land inheritance practices, finding a difference between legal land ownership and actual possession and use. These consequences travel generation after generation and both increase the possibilities of exacerbating the inter- and intra-religious conflicts and tensions within Bangladesh and often aggravate the insecurities and vulnerabilities of the Christian minorities.